Media Book Stories Regarding Forms of Bullying in Classical Guidance Activities for Elementary School Students - Prasetya, Yunisa Asih; Hanim, Wirda; Fridani, Lara (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2019)
Bullying cases are still rife in the educational environment, including in elementary school education units. Students tend not to understand bullying behavior, so many children think this is normal. Students taunt each other, cheer, make fun of, or joke through physical actions are behaviors that are often carried out by students and are sometimes allowed by adults around them without thinking further about the negative impact. Therefore, students need to get information about bullying related to meaning, type, influence, and how to deal with bullying. Prevention and handling of bullying cases in the school environment not be separated from the involvement of the roles of all parties, namely school policies, teachers, and parents. The existence and function of guidance and counseling teachers in elementary schools to prevent and reduce cases of bullying. Guidance and counseling teachers must be able to think creatively, innovatively in providing services to students to achieve developmental tasks can be fulfilled. One of them is to try to find the right method in delivering essential services regarding bullying cases. The storytelling method using storybook media can be used to explain the picture of bullying to elementary school students. In providing services to students so that efforts to achieve developmental tasks can be fulfilled. One way is to keep trying to find the right method in delivering essential services regarding bullying cases. The storytelling method using storybook media can be used to explain the picture of bullying to elementary school students. In providing services to students so that efforts to achieve developmental tasks can be fulfilled. One of them is to try to find the right method in delivering essential services regarding bullying cases. The storytelling method using storybook media can be used to explain the picture of bullying to elementary school students. Stories allow children to express fantasies and explore conflict situations and enable children to deal with important issues and feelings. Using attractive media can optimize the achievement of students in participating in classical guidance activities in essential services, one of which is by using storybook media.